Studies on the Regulation and Molecular Mechanism of Panax Ginseng Saponins on Senescence and Related Behaviors of Drosophila melanogaster - Zhao, Qiushi; Liu, Ying; Zhang, Siyu; Zhao, Yuchu; Wang, Chenxi; Li, Keqiang; Jin, Zecheng; Qiao, Juhui; Liu, Meichen (Frontiers in Aging Neuroscience, 2022)
In an increasingly aged global population, achieving healthy life expectancy through natural and safe drug interventions is highly desirable. Here we show that total ginsenosides (TGGR), the main active components in the traditional Chinese medicine, ginseng, promote longevity across species. In Drosophila, an intriguing effect of TGGR on lifespan was the relatively narrow treatment window to elicit long-term benefits. TGGR administration during early adulthood, and especially during midlife, was sufficient to extend lifespan in both sexes. TGGR did not increase lifespan by reducing food intake or reproductive capacity; rather, TGGR increased the fertility of male Drosophila. TGGR augmented healthspan readouts associated with youth and with healthy aging, such as motility, intestinal barrier integrity, and biorhythm homeostasis. TGGR treatment also improved some types of stress resistance in both sexes, including increased tolerance to starvation and oxidation, and shifting ‘aged’ gene expression patterns toward ‘healthy’ patterns seen in the young. Gene expression, pharmacological and genetic epistatic analyses demonstrated that TGGR effects require normal expression of genes involved in insulin, TOR and MAPK signaling. The positive effects of TGGR on both healthspan and lifespan, coupled with its mechanism of action via evolutionarily conserved signaling pathways, demonstrate it to be a promising anti-aging drug.